Salafi youth activism in Britain: a social movement perspective - Emmerich, Arndt (Journal of Muslims in Europe, 2020)
The article uses insights from social movement theory (SMT) to comprehend how a local Salafi youth group in Britain promotes ideas, recruits new members and shares organisational features with other forms of collective action. A social movement perspective has not been employed systematically for the study of quietest Salafi activism, partially because of an urban, elite bias within SMT and fusion of SMT with terrorism studies. This omission within SMT is discussed, stressing that, although insights from SMT can be useful for understanding Salafi youth groups, its current application may further contribute to the stereotyping of Muslim minorities in Europe.